2021
DOI: 10.9734/ajpas/2021/v12i330287
|View full text |Cite
|
Sign up to set email alerts
|

Sarima Modeling of Monthly Temperature in the Northern part of Ghana

Abstract: The Sarima model is used in this study to forecast the monthly temperature in Ghana's northern region. The researchers used temperature data from January 1990 to December 2020. The temperature data was found to be stationary using the Augmented Dickey Fuller (ADF) test. The ACF and PACF plots proposed six SARIMA models: SARIMA (1,0,0) (1,0,0) (12), SARIMA (2,0,0) (1,0,0) (12), SARIMA (1,0,1) (1,0,0) (12), SARIMA (0,0,1) (1,0,0) (12), SARIMA (0,0,1) (0,0,1) (12), SARIMA (0,0,1) (0,0,1) (12). The best model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The study on the SARIMA model has shown that this model has various uses in forecasting data related to -Weather and Temperature forecasting [33], Tourism [34], fire frequency or accidents forecasting [35], the financial sector [36], and healthcare industry [37]. Talking about the healthcare industry, the current paper deals with the analysis and forecasting of region-wise smart lockdowns.…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study on the SARIMA model has shown that this model has various uses in forecasting data related to -Weather and Temperature forecasting [33], Tourism [34], fire frequency or accidents forecasting [35], the financial sector [36], and healthcare industry [37]. Talking about the healthcare industry, the current paper deals with the analysis and forecasting of region-wise smart lockdowns.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Some of the commonly used examples in the Machine Learning domain have been hereby stated with a small summary of the objective and the results produced by SARIMA Models as various different applications. Paper [33] describes a SARIMA Model capable of forecasting monthly temperature values in Ghana's northern area. The SARIMA(1,0,0)(1,0,0)( 12) is the best-fitting model, according to the results.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation